A fluorescent chemodosimeter based on rhodamine derivative for detection of Hg(II) ions studied by using the density functional theory - Quy, Phan Tu; Hien, Nguyen Khoa; Tung, Truong Quy; Quang, Duong Tuan (Vietnam Journal of Chemistry, 2017)
The synthesis, characteristics and applications of the rhodamine derivative-based fluorescent chemodosimeter RT for detection of mercury ions have been studied at the B3LYP/LanL2DZ level of theory. The calculated results confirmed the presence of spirolactam ring in RT molecule. The Hg(II) ions reacted with RT to form RG, accompanied by the formation of guanidine ring and the spirolactam ring-opening in RG, turning on the fluorescence of RG. These results were in a good agreement with experimental investigations. It indicated that the quantum chemical calculations could be used well for the design, synthesis of the fluorescent chemodosimeter. Keywords. Fluorescence, chemodosimeter, rhodamine, mercury, DTF, TD-DFT.